Pengembangan Bahan Ajar E-book Menggunakan Aplikasi Heyzine Pada Subtema Benda Tunggal dan Campuran: Penelitian Research and Development pada Peserta Didik Kelas V di Sekolah Dasar Negeri Bojong 02 Kecamatan Kemang Semester Genap Tahun Pelajaran 2023/2024 - Risa, Mahda; Irdiyansyah, Iyan; Mirawati, Mira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mahda Risa 037120058. Development of E-Book Teaching Materials Using the Heyzine Application on the Subtheme of Single and Mixed Objects. The research subjects were 32 students of grade V SDN Bojong 02, Kemang District, the research was conducted in the even semester of the 2023/2024 school year. The research method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Analyzing the needs of the learning process still using printed books, then planning the preparation of e-book teaching materials. Continued by developing products that have been designed for media, language, and material experts. Implementing it to grade V SDN Bojong 02 and evaluating the results of student responses to the products that have been developed. The results of the study showed that the development of this e-book teaching material obtained 94% from media experts, 96% from language experts, 100% from material experts in the field of evaluation, and 82.25% from student responses. Based on these results, it can be concluded that e-book teaching materials using applications Heyzine are very suitable for use in the learning process.